Types and Abundance of Beach Litter on the East Coast of Karimun Island, Riau Islands - Ranti, Putri; Amin, Bintal; Mubarak, Mubarak (Journal of Coastal and Ocean Sciences, 2025)
This research was conducted in January 2025 on the East Coast of Karimun Island, Riau Islands Province. This study aimed to determine the type and abundance of Beach Litter on the East Coast of Karimun Island, Riau Islands Province. The method used in this research is a survey method with direct observation and data collection at the research location. The waste data obtained was analyzed statistically, and then the results were presented descriptively, referring to the supporting literature. The most dominant type of waste is plastic-type at Station I (Coastal Area), and the last type of waste obtained is rubber-type at Station II (Ketam Beach), for the results of the highest abundance between stations is found at Station I, namely 7,12 units/m² and the lowest abundance at station II, namely 0,84 units/m². In comparison, the abundance results between sampling times obtained the highest abundance during the Weekend of 19,48 units/m² and the lowest abundance during Weekday of 11,88 units/m². Based on the difference test of abundance between stations and between sampling times, there is a real or significant difference (P <0,05)